Glucagon Shows Higher Sensitivity than Insulin to Grapeseed Proanthocyanidin Extract (GSPE) Treatment in Cafeteria-Fed Rats - Grau-Bové, Carme (Nutrients, 2021)
The endocrine pancreas plays a key role in metabolism. Procyanidins (GSPE) targets β-cells and glucagon-like peptide-1 (GLP-1)-producing cells; however, there is no information on the effects of GSPE on glucagon. We performed GSPE preventive treatments administered to Wistar rats before or at the same time as they were fed a cafeteria diet during 12 or 17 weeks. We then measured the pancreatic function and GLP-1 production. We found that glucagonemia remains modified by GSPE pre-treatment several weeks after the treatment has finished. The animals showed a higher GLP-1 response to glucose stimulation, together with a trend towards a higher GLP-1 receptor expression in the pancreas. When the GSPE treatment was administered every second week, the endocrine pancreas behaved differently. We show here that glucagon is a more sensitive parameter than insulin to GSPE treatments, with a secretion that is highly linked to GLP-1 ileal functionality and dependent on the type of treatment.